Application of moisture transfer models to solids drying - Akpinar, EK; Dincer, I (Sage Publications Ltd, 2005)
In this paper, a comprehensive experimental investigation is conducted to measure the moisture content distributions within slab cut potato pieces during drying at temperatures of 60, 70, and 80 degrees C and flow velocities of 1.0 and 1.5 m/s. Four drying models are employed to determine the drying process parameters (drying coefficient, lag factor, and half-drying time) and moisture transfer parameters (moisture diffusivity and moisture transfer coefficient), and to calculate moisture content distributions and compare them with extensive sets of experimental moisture data measured during the drying of slab cut potato slices at different drying air temperatures and flow velocities. Good agreement is obtained between the calculations and experimental measurements for the cases. In addition, experimental drying times are determined and compared with those obtained by the four different drying models. The results show that all four models are well able to determine the drying parameters and moisture content distributions. The experimental data and model findings are expected to be useful to the drying industry.
Keywords: drying; drying parameters; energy use; moisture transfer